Proceedings Electronic Components and Technology, 2005. ECTC '05.
DOI: 10.1109/ectc.2005.1441300
|View full text |Cite
|
Sign up to set email alerts
|

Whisker formation on matte Sn influencing of high humidity

Abstract: With the 1 st of July 2006 as deadline for the European RoHS directive approaching fast, the need for conversion of SnPb plated components to Pb-free alternative is increasing. Most component suppliers are looking at pure Sn plated or Sn-alloys electroplating as an alternative for the SnPb plating. However, electroplated Sn and Sn-alloys are associated with spontaneous whisker growth.In these past 4 years the E4 (Freescale Semiconductor, Infineon, STMicroelectronics and Philips) have extensively studied matte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…Su and coworkers observed that decreasing the humidity from 93%RH to 85%RH in a 2000-h exposure at 60 C reduced the number of leads with whiskers by a factor of 10, decreased the whisker lengths, and prevented localized corrosion [17]. Other researchers observed similar results for 85%RH/55C test conditions [18].…”
Section: B High-temperature/humidity Conditionsupporting
confidence: 65%
See 1 more Smart Citation
“…Su and coworkers observed that decreasing the humidity from 93%RH to 85%RH in a 2000-h exposure at 60 C reduced the number of leads with whiskers by a factor of 10, decreased the whisker lengths, and prevented localized corrosion [17]. Other researchers observed similar results for 85%RH/55C test conditions [18].…”
Section: B High-temperature/humidity Conditionsupporting
confidence: 65%
“…Corrosion may cause a new whisker mechanism or may alter factors involved in whisker growth, such as stress [18] or diffusion. However, corrosion is not the only explanation for whisker growth, since we observe whiskers in ambient testing and thermal cycle testing, which does not create localized corrosion.…”
Section: B High-temperature/humidity Conditionmentioning
confidence: 99%
“…Especially halides and flux residues after soldering processes are presumed to function as initiators for chemical reactions on the metal surface [6]. Corrosion products located between columnar deposited grains of a tin surface are presumed to induce significant stress levels, which initiate whisker growth [5,6]. To prove this model, it is of utmost importance to analyze the corrosion process itself and to know which tin(II) and or tin(IV) chemical species are located on the metal surface to induce stress levels.…”
Section: Introductionmentioning
confidence: 99%
“…When considering applications of high reliability such as automobiles, we need to understand the exact mechanism of the whisker growth in high humid environments and during temperature change, and then provide feedback to package design as well as plating and assembly processes to minimize whiskering. However, until now, there have been few studies on whiskering in these two conditions, especially for alloy42 LF packages [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In the ambient storage condition, as the result of the formation of Cu 6 Sn 5 intermetallic growth in tin grain boundaries, compressive stress is generated inside the tin film, thereby atoms move from the highly compressive stressed film/substrate region to the near-zero stressed whisker grains through grain boundaries [2]. In the elevated temperature and high humid environments oxidation and corrosion of tin-plating layer are the root-cause of the whiskering [3,4]. Osenbach et al identified the corrosion products as dense mixture of crystalline SnO 2 and Sn by transmission electron microscopy analysis and concluded that injection of oxygen into the tin film creates localized compressive stress [4].…”
Section: Introductionmentioning
confidence: 99%